Sialic acid and vascular cell adhesion molecule-1 as early markers in the first degree relatives of type 2 diabetes mellitus patients - Qvist, R.; Ismail, I.S.; Muniandy, S.; Lee, H.F.; Vellasamy, K.M.; Chinna, K.; Zaini, A. (2006)
Levels of sialic acid and Vascular Cell Adhesion Molecule-1 (VCAM-1) in the first degree relatives of type 2 diabetes mellitus patients and their possible role as an early marker of the prediabetic stage were studied in 74 controls and 150 first degree relatives. The total sialic acid concentration was significantly higher (p<0.05) in the first degree relatives compared to the control subjects. Amongst the offsprings, the total sialic acid concentration was significantly higher in the offspring with Normal Glucose Tolerance (NGT) than those with Impaired Glucose Tolerance (IGT). However the level of VCAM-1 did not differ amongst the controls and the first degree relatives. The total cholesterol and triglycerides were significantly higher (p<0.05) in the offspring with IGT when compared to the control subjects and the offspring with NGT. The above data suggests that desialylation of the vascular endothelium is an early event that precedes the expression of IGT or any lipid changes in asymptomatic offspring of one type 2 diabetic parent.